Experimental Study of Byzantine Chafing Dishes - Georgia Vakasiras (EXARC Journal)
This article sets out to examine the production, function, and use of Byzantine chafing dishes, which have been largely neglected by academic literature. As no practical engagement with chafing dishes has been previously attempted, experimental archaeology was chosen as a methodological tool capable of testing hypotheses associated with these wares and generating new research questions. Three chafing dishes were crafted by ceramist Alexandra Theodosiou, modelled on chafing dish 6260a and its lid 6260β from Thebes, to understand the assembly stages of the different compartments of this multi-featured form. The models were then employed to debate questions related to function. Three prominent hypotheses regarding the heating means used to warm a chafing dish (lamp, candle, charcoal) were put into trial, so as to match use wear traces resulting from thermal stress (soot deposits) against corresponding combustible material. This could, consequently, enable reflection on the archaeological comparanda and conclude, which of the above methods would have been applied. Temperature was recorded as well as an overall reporting on the performance of each specimen. The results, though inconclusive, were taken into consideration, when discussing the use of chafing dishes, and, in particular, their association with garum.